Exploiting the Interplay between Liquid-Liquid Demixing and Crystallization of the PVDF Membrane for Membrane Distillation. (5th December 2018) - Nawi, N. I. M.; Bilad, M. R.; Nordin, N. A. H. M.; Mavukkandy, M. O.; Putra, Z. A.; Wirzal, M. D. H.; Jaafar, J.; Khan, Asim L.
Abstract : Membrane distillation (MD) purifies water by transporting its vapor through a hydrophobic membrane. An ideal MD membrane poses high water flux and high fouling, scaling, and wetting resistances. In this study, we develop polyvinylidene fluoride (PVDF) membranes for MD by focusing on reduction of PVDF degree of crystallinity. We explore the roles of dope solution temperature in dictating the phase separation mechanisms as well as the structure and the performance of semicrystalline PVDF membranes. DSC spectra show that higher dope solution temperature depresses crystallinity via formation of imperfect crystal. Such findings were also supported by FTIR and XRD results. The SEM images reveal formation of spherulite-like morphology in the membrane matrices for membranes prepared from high temperature dope solutions. A good balance between solid-liquid and liquid-liquid phase separations that offers low degree of crystallinity was found at a dope solution temperature of 60°C (PVDF-60), which showed the MD flux of 18 l/m 2 h (vs. 6 l/m 2 h for temperature of 25°C, as a benchmark) and nearly complete salt rejection when run at hot and cold temperatures of 65°C and 25°C, respectively. The PVDF-60 shows a high wetting resistance and stable MD flux of 10.5 l/m 2 h over a 50 h test for treating brine solution as the feed (70 g NaCl/l).